Twelve Asteraceae Species as Tyrosinase Inhibitors: Selection and Assumption of Active Compounds - Veby Tri Yani; Irma Herawati Suparto; Batubara, Irmanida (Tropical Biopharmaca Research Center, IPB University, 2022)
Some Asteraceae plants have phytochemicals that are commonly used to treat some illness. However, research on the use of Asteraceae plants as tyrosinase inhibitor agents is still rare. Therefore, this study aims to select the most active fraction of Asteraceae species as tyrosinase inhibitors and suspect active compounds that play a role in it. About 12 species from Asteraceae are extracted using water. The resulting filtrate is partially fractionated using chloroform to obtain water extracts, water fractions, and chloroform fractions. Each extract and fraction of each plant determined the activity of its tyrosinase inhibitor using a microplate reader (ELISA) with L-DOPA as the substrate. Thitonia diversipholia water fraction provided the best activity of all the samples tested with the smallest IC50. The active compounds contained are analyzed using LC-MS / MS. Compounds that act as tyrosinase inhibitors are alkaloid group that dominate the plant, namely trigonelline.